The Implications Of Gap And Risk On Profitabilty - MURAD @ MANSOR, SHAIFUL NIZAN (2005)
Against the backdrop of rapidly changing financial landscape and increased uncertainty, the bank will always need to regularly review its risk management process in order to ensure safe daily operations and sound policies. Every commercial bank in Malaysia is having its own unit in monitoring and analyzing risks in banking business that they are onto. It is vital in order to ensure that their financial system is best placed to serve the economy and survived.